2020
DOI: 10.1111/cns.13439
|View full text |Cite
|
Sign up to set email alerts
|

B3GNT5 is a novel marker correlated with stem‐like phenotype and poor clinical outcome in human gliomas

Abstract: Glioblastoma (GBM) is a grade IV brain tumor, which is one of the most malignant tumors associated with a reduced long-term survival despite aggressive treatment strategies, such as surgery, radiotherapy, and chemotherapy. 1 Recent studies have shown that glioma stem cells (GSCs), which resemble normal stem cells in terms of potential self-renewal and terminal differentiation, are involved in tumor development, therapeutic resistance, and recurrence. 2 Therefore, targeting the stem cell characteristics of GSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…Functionally, the overexpression of B3GNT5 relieved the sh-2HG-1-induced inhibition of cell proliferation, migration and invasion. These results were consistent with the previous study in human glioma in which B3GNT5 was revealed to act as a tumor promoter ( 35 ). However, a major limitation of the current study is that B3GNT5-related signaling pathways and the effect of MIR4435-2HG in liver cancer in vivo were not comprehensively studied and thus will be explored further in the future.…”
Section: Discussionsupporting
confidence: 93%
“…Functionally, the overexpression of B3GNT5 relieved the sh-2HG-1-induced inhibition of cell proliferation, migration and invasion. These results were consistent with the previous study in human glioma in which B3GNT5 was revealed to act as a tumor promoter ( 35 ). However, a major limitation of the current study is that B3GNT5-related signaling pathways and the effect of MIR4435-2HG in liver cancer in vivo were not comprehensively studied and thus will be explored further in the future.…”
Section: Discussionsupporting
confidence: 93%
“…This proves that the 11 key genes we found are meaningful for clinical prognosis of glioma. Among the 11 genes, 7 of them (i.e., B3GNT5, BICD1, KIF3A, HAUS1, MTMR3, ITGB3 and EXTL3) have been confirmed to be associated with the prognosis of glioma (Kim et al, 2011;Sumazin et al, 2011;Huang et al, 2017;Zhou et al, 2018;Jeong et al, 2020;Li et al, 2020;Wang et al, 2020). Our findings imply that the functions of these genes in glioma prognosis may be related to the methylation regulation of their AS events.…”
Section: Influence Of the Me-sqtl Genes On Clinical Prognosis Of Gliomamentioning
confidence: 53%
“…ACSL1 exists in cells of the liver, heart and fat, as is considered to affect activation fatty acid synthesis of triglycerides through the peroxisome proliferator-activated receptor γ pathway (44). B3GNT5 has been suggested as the key glycosyltransferase in the biosynthesis of the (neo-)lacto series of glycosphingolipid in regulating malignancy of glioblastoma multiforme (45). This result implies that the etiology of AMI is associated with genes related to intravascular disease, immune response and brain-derived factor regulation system, suggesting that ACSL1, B3GNT5 and MGAM may be also used as biomarkers for gene expression in early AMI.…”
Section: Discussionmentioning
confidence: 99%